Perancangan Web Marketplace Toko Sepatu Akshara.co dengan Sistem Rekomendasi Menggunakan Perhitungan Algoritma Apriori - Dennise Gibran Manoppo; M Iwan Wahyudin; Winarsih Winarsih (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
In this advanced period, shoes arsse an essential requirement for practically all circles, a great deal of Online business organizations are arising and filling quickly in Indonesia, in addition to the quantity of dynamic web clients in Indonesia is expanding quickly from one year to another. Making Online business organizations contend to explore different techniques as far as advertising to draw in more individuals to purchase the items they offer to get by in the online businss market rivalry in this country, one illustration of a promoting methodology to draw in and increment public premium buys is the execution of the merchandise proposal framework in Online business. Consequently, in this investigation, an electronic Web based business will be made that can help Internet business organizations anticipate purchaser premium in a thing and afterward prescribe it to draw in more purchasers who come. This Web based business utilizes the Apriori Calculation way to deal with get more exactness in the information handling measure. The outcomes acquired from that examination are the making electronic Web based business by executing the suggestion technique showed on the "Akshara.co" framework include